Synthetic amides toxic to the leaf-cutting ant Atta sexdens rubropilosa L. and its symbiotic fungus - Pagnocca, F. C.; Victor, SR; Bueno, F. C.; Criostomo, F. R.; Castral, T. C.; Fernandes, J. B.; Correa, A. G.; Bueno, O. C.; Bacci, M.; Hebling, MJA; Vieira, P. C.; da Silva, MFGF (Wiley-Blackwell, 2006)
1 Nine synthetic amides similar to natural N-piperidine-3-(4,5-methylenedioxyphenyl)-2-(E)-propenainide and N-pyrrolidine-3-(4,5-methylenedyoxiphenyl)2-(E)-propenamide were synthesized and identified by their spectroscopic data.2 the toxicity of these synthetic amides to the Atta sexdens rubropilosa workers and the antifungal activity against Leticoagaricus gongylophorus, the symbiotic fungus of the leaf-cutting ants, were determined.3 Workers ants that were fed daily on an artificial diet to which these compounds were added had a higher mortality rate than the controls for N-pyrrolidine-3(3',4'-methylenedioxyphenyl)-2-(E)-propenamide and N-benzyl-3-(3',4'-methylenedioxyphenyl)-2-(E)-propenamide at a concentration of 100 mu g/mL.4 the completely inhibition (100%) of the fungal growth was observed with N-piperldine-3-(3',4'-methylenedioxyphenyl)-2-(E)-propenamide and N,N-diethyl-3-(3',4'-methylenedioxyphenyl)-2-(E)-propenamide at concentrations of 50 and 100 mu g/mL and N-pirrolidine-3-(3',4'-methylenedioxyphenyl)-2-(E)-propenamide at a concentration of 100 mu g/mL.5 the possibility of controlling these insects in the future using synthetic piperamides that can simultaneously target both organisms is discussed.
Keywords: antiftingal activity; Atta sexdens rubropilosa; insecticidal activity; leaf-cutting ants; Lelicoagaricus gongylophorus; piperamides